Hope, health and wealth - Pereyra Lavandina, Mario (2010)
The author overviews the most important researches made on patients (and non-patients too), from different health care areas, to identify the influence that the patients’ optimism or pessimism may have on their physical condition. These contributions provided amazing information and unsuspected functions, wherein it is agreed that to have hope is the true “laboratory of health”.